2005
DOI: 10.1002/cbf.1255
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamins C and E on oxidative processes in human erythrocytes

Abstract: The oxidative action of 1 mmol l(-1) phenylhydrazine hydrochloride (PH) was studied on human erythrocytes treated with the antioxidants vitamin C (vit. C) and vitamin E (vit. E). The erythrocytes were resuspended in PBS to obtain 35% cell packed volume, and then submitted to the oxidative action of PH for 20 min, with or without previous incubation for 60 min with vit. C or vit. E. Heinz bodies and methemoglobin formation by PH were inhibited in the presence of vit. C. At the concentration of 90 mmol l(-1), vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 20 publications
3
12
0
2
Order By: Relevance
“…Vitamins C and E contribute to the decrease in oxidative stress caused by PHZ in vitro by inhibiting Heinz bodies and methemoglobin formation. [38] Flavonoids are a broad class of plant phenolics that are known to possess a well-established protective effect against membrane lipoperoxidative damages. Oxidative damage of erythrocytes has been implicated in the reduced survival of erythrocytes during Leishmanial infection.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamins C and E contribute to the decrease in oxidative stress caused by PHZ in vitro by inhibiting Heinz bodies and methemoglobin formation. [38] Flavonoids are a broad class of plant phenolics that are known to possess a well-established protective effect against membrane lipoperoxidative damages. Oxidative damage of erythrocytes has been implicated in the reduced survival of erythrocytes during Leishmanial infection.…”
Section: Discussionmentioning
confidence: 99%
“…Alpha-tocopherol does have the ability to inhibit chemical oxidation of RBCs; 30 however, the extent to which such is a normal pathway during RBC storage is unclear and has only been tested in an in vitro setting. 31 Of interest, it has recently been reported that vitamin C and N-acetylcysteine mitigate oxidative stress in in vitro human RBC studies.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E, a constituent of the plasma membrane, then an effective antioxidant, scavenges peroxide free radicals and converts them to less toxic lipid hydroperoxides, thereby protecting the cell membrane and decreasing hemolysis (Niki and Noguchi, 2004). The benefits of this vitamin have been reported in human RBC when challenged with phenylhydrazine hydrochloride (Claro et al, 2006). However, according to Mendanha et al, (2012), AA and α-tocopherol are able to prevent oxidative hemolysis and TBARS production, but can not decrease the membrane rigidity when RBCs are exposed to H 2 O 2 .…”
Section: Oxidative Stress and Protection By Antioxidant Vitaminsmentioning
confidence: 99%